2003
DOI: 10.1067/mhn.2003.67
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Yield in Neck Dissection and the Likelihood of Metastases

Abstract: In T1 and T2 cases of HNSCC, nodal yield >20, increased age, male sex, and primary site correspond with an increased likelihood of finding cervical metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…One must also consider that the neck is an infrequent site of isolated recurrence and lymph node metastases reveals an aggressiveness phenotype which is not only regional. Agrama et al 3 reported a higher probability of finding metastases when more than 20 lymph nodes are dissected. Moreover, there is an expectation that approximately 7% of the pN0 cases have unidentified micrometastases in routine sections 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One must also consider that the neck is an infrequent site of isolated recurrence and lymph node metastases reveals an aggressiveness phenotype which is not only regional. Agrama et al 3 reported a higher probability of finding metastases when more than 20 lymph nodes are dissected. Moreover, there is an expectation that approximately 7% of the pN0 cases have unidentified micrometastases in routine sections 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Metastatic lymph nodes represent one of the most relevant aspects associated with treatment, characterizing an advanced clinical stage (stages III or IV), and it is associated with a 50% reduction in survival 1 . Although the number of lymph nodes removed is prognostically relevant in other areas of the body (colon and breast), very few studies have assessed their meaning in head and neck tumors [2][3][4][5][6] . Moreover, the number of lymph nodes removed may also be an indicator of how radical the dissection is as a staging method.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors claim that the number of removed lymph nodes carries prognostic value in pN0 patients, to suggest a more accurate staging or a more responsive immune system [5][6][7][8][9] . The presence of metastatic lymph nodes is one of the most significant prognostic indicators in malignant had and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastasis lead to a reduction of approximately 50% on survival, and prognosis is significantly worse when three or more metastatic lymph nodes are found 10,11 . The length of the neck clearance procedure, the surgical approach, and the level of histopathological investigation determine the degree to which lymph nodes are examined for metastasis detection and, thus, the likelihood of finding metastases in the lymph nodes at risk 6 . Thus, it is expected that these factors determine the pN lymph node stage (negative or positive).…”
Section: Discussionmentioning
confidence: 99%
“…A nyirokcsomóhozam prognózisra gyakorolt hatása hasonlónak bizonyult a papillaris pajzsmirigyrákok [13,14], valamint a szájüreg [12,[15][16][17][18], az oropharynx [17] és a hypopharynx [17,19] laphámrákjai esetében is. Egy, a közelmúltban megjelent multicentrikus tanulmány megerősítette a nyirokcsomóhozam független prognosztikai szerepét a cN0 nyaki stádiumú szájüregi laphámrák miatt elektív és szelektív nyaki dissectión át-esett betegeknél is [18].…”
Section: öSszefoglaló Közleményunclassified